Avaliação da eficiência da aplicação de recursos no Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Sul - Hining, Luiz Antônio (My University, 2026)
Public spending in Brazil, especially in education, has long been a topic of debate and discussion at all levels of government, being subject to various assessments, interpretations, and criticisms, whether regarding the allocation or the application of resources. Within this context, the present study aimed to analyze the efficiency in the allocation of resources at the Federal Institute of Education, Science and Technology of Rio Grande do Sul (IFRS). To achieve this objective, the Data Envelopment Analysis (DEA) method was applied. This non-parametric multivariate technique evaluates the efficiency of Decision Making Units (DMUs), which, in this study, corresponded to the 17 campuses of the IFRS. Based on the literature, three input and two output variables were selected, and the classical input-oriented BCC DEA model was applied to optimize the use of resources while maintaining the achieved results. The results indicated high average efficiency levels during the period from 2019 to 2024, with an overall variation around 0.95 and a peak of 0.98 in 2022, demonstrating stability and sound performance in input management. However, heterogeneity among campuses was observed, with three units achieving full efficiency (1.00), two reaching nearoptimal levels (0.99), and the others ranging from 0.87 to 0.91, indicating internal differences and opportunities for improvement. The longitudinal analysis showed that such variations may be associated with campus size, course composition, and budget execution capacity. It is concluded that the IFRS demonstrated efficient management of public resources, maintaining balance and stability between inputs and outcomes, confirming patterns similar to those observed in previous studies on Federal Institutes and public universities. The application of DEA proved to be an effective tool to support planning and decision-making, contributing to greater efficiency and transparency in the management of the institution's budgetary resources. [resumo fornecido pelo autor]
O gasto público no Brasil, em especial na educação, sempre foi motivo de debate e discussões em qualquer nível de governo, estando sujeito a avaliações, interpretações e críticas, seja pela disponibilização de recursos, seja pela sua destinação e aplicação. Inserido nesse contexto, o presente trabalho teve como objetivo analisar a eficiência da aplicação de recursos no Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Sul (IFRS). Para alcançar esse objetivo, foi utilizado o método da Análise Envoltória de Dados - Data Envelopment Analysis (DEA). Esse método consiste em uma técnica multivariada não paramétrica que analisa a eficiência de Unidades Tomadoras de Decisão - Decision Making Units (DMUs) que, no caso do presente estudo, foram os 17 campi pertencentes ao Instituto Federal de Educação do Rio Grande do Sul. Tendo como base a literatura, foram selecionados três inputs e dois outputs, e foi aplicado o modelo DEA clássico BCC, orientado a inputs, visando otimizar a aplicação de recursos, mantendo os resultados já obtidos. Os resultados indicaram elevados níveis de eficiência média ao longo do período de 2019 a 2024, com variação próxima de 0,95 e pico de 0,98 em 2022, revelando estabilidade e bom desempenho da instituição na gestão dos insumos. Observou se, contudo, heterogeneidade entre os campi, com três unidades apresentando eficiência plena (1,00), duas próximas desse patamar (0,99) e variação de 0,87 a 0,91 entre as demais, demonstrando diferenças internas que apontam para oportunidades de aprimoramento. A análise longitudinal mostrou que essas variações podem estar associadas ao porte das unidades, à composição dos cursos e à capacidade de execução orçamentária. Conclui-se que o IFRS apresentou gestão eficiente dos recursos públicos, com estabilidade e equilíbrio entre insumos e resultados, confirmando padrões semelhantes aos observados em estudos anteriores sobre Institutos Federais e universidades públicas. A aplicação da Análise Envoltória de Dados demonstrou ser um instrumento eficaz de apoio ao planejamento e à tomada de decisão, contribuindo para o aprimoramento da eficiência e da transparência na gestão dos recursos orçamentários da instituição. [resumo fornecido pelo autor]
Keywords: Administração financeira; Orçamento nas empresas - Avaliação; Finanças públicas - Avaliação; Investimentos públicos - Educação; Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Sul - Estudo de caso; Financial administration; Budget in business - Evaluation; Finance, Public - Evaluation; Public investments - Education; Federal Institute of Education, Science and Technology of Rio Grande do Sul - Case Study